National Hospital Ambulatory Medical Care Survey, 2004 ([Verlag nicht ermittelbar], 2006)
The National Hospital Ambulatory Medical Care Survey (NHAMCS) provides data from samples of patient records selected from emergency departments (EDs) and outpatient departments (OPDs) of a national sample of hospitals. The resulting national estimates describe the use of hospital ambulatory medical care services in the United States. For the 2004 survey, data were collected from 204 OPDs and 458 EDs. Among the variables included are age, race, and sex of the patient, reason for the visit, physician's diagnoses, cause of injury, surgical procedures (OPDs only), medication therapy, and expected source of payment. For 2004, additional updates and revisions have been made to the drug characteristics data. The variables CSTRATM and CPSUM have been added to assist in the computation of variances.